The Role of Parental Investments for cognitive and noncognitive skill formation - Evidence for the first 11 years of life - Karsten Reuß; Katja Coneus; Manfred Laucht (Verein für Socialpolitik, 2010)
This paper examines the impact of parental investments on various skills during childhood using the Mannheim Study of Children at Risk (MARS). Our work offers three important innovations. First, we use reliable measures of the child's cognitive, mental and emotional skills as well as accurate measures of parental investment derived from a longitudinal epidemiological cohort study. Second, we estimate latent factor models to account for unobserved characteristics of children. Third, we examine the skill development for girls and boys, separately, as well as for children who were born with either organic or psychosocial risk. We find a decreasing impact of parental investments on cognitive and mental skills, while emotional skills seem to be unaffected throughout childhood. Thus, initial inequality increases during childhood. Since families are the main sources of education during the first years of a child's life, our results have important implications for the quality of the parent-child interaction.
Keywords: I21; J24; J31; 330; cognitive skills; noncognitive skills; critical and sensitive periods; self-productivity; inequality; organic risk; psychosocial risk